2005
DOI: 10.1159/000089708
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Systemic Lupus Erythematosus in End-Stage Renal Disease Patients: Study in a Brazilian Cohort

Abstract: Background: Dialysis has been associated with lupus remission. We studied the prevalence of systemic lupus erythematosus (SLE) as a cause of end-stage renal disease (ESRD) in the metropolitan area of Rio de Janeiro and assessed disease activity in SLE patients on dialysis. Methods: Of 3,535 ESRD patients, 63 had SLE (1.8%). Fifty-seven entered the study (54 females, 3 males, 38 ± 10 years). Hemodialysis consisted of 3 sessions per week of about 4 h duration, blood flow of about 400 ml/min, bicarbonate dialysat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 36 publications
0
17
0
1
Order By: Relevance
“…Ribeiro et al [20] performed a cohort including 57 patients with SLE and ESRD and compared with a control group of 57 non-lupus individuals all under hemodialysis. Applying the criteria non-renal SLEDAI >0, use of at least 20 mg/day of prednisone, and/or any dose of another activity-controlling drug to define disease activity, it was observed that 48 patients (84%) had an active SLE and 21 controls (37%) exhibited an "apparently active" disease.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ribeiro et al [20] performed a cohort including 57 patients with SLE and ESRD and compared with a control group of 57 non-lupus individuals all under hemodialysis. Applying the criteria non-renal SLEDAI >0, use of at least 20 mg/day of prednisone, and/or any dose of another activity-controlling drug to define disease activity, it was observed that 48 patients (84%) had an active SLE and 21 controls (37%) exhibited an "apparently active" disease.…”
Section: Resultsmentioning
confidence: 99%
“…As pointed out above, the diminishing in the disease activity after ESRD was not a universal finding, and there may be various explanations for the great variability of the results found in the studies, such as: (a) adoption of different clinical and serological criteria to define a lupus flare; (b) the follow-up period after dialysis was very distinct and might have over-or underestimated the number of disease reactivations. Some studies excluded from the analysis patients with SLE and ESRD who remained less than 6 months in dialysis [18,[20][21][22], what may have contributed to underestimate the occurrence of lupus flares, as some articles showed greater number of deaths related to SLE activity in the beginning of the dialysis [11,15]; (c) the use of a control group for comparison was not a constant in every study, and among those controlled, there was a large variation in the characteristics of the controls-mainly in respect of the presence or absence of SLE; and (d) the adoption of different types of renal replacement therapy between the studies (hemodialysis, peritoneal dialysis, and renal transplantation), although some authors [4,22] have demonstrated a lack of statistically significant differences in patients undergoing hemodialysis when compared to those treated by peritoneal dialysis. Accordingly, Goo et al [22] found that the disease activity measured by SLEDAI did not significantly differ among the group of patients who were treated by hemodialysis, peritoneal dialysis, or renal transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…El inicio de TRR suele asociarse a disminución de actividad del LES 31 . La inmunosupresión en este caso estará indicada para el control de enfermedad extra-renal.…”
Section: ¿Deben Mantenerse Inmunosuprimidos Los Pacientes Que Inicianunclassified
“…In some cases, reactivation of SLE does occur in patients under chronic dialysis treatment [4,5]. However, the onset of SLE long after the initiation of renal replacement treatment has been rarely reported.…”
Section: Introductionmentioning
confidence: 99%